How perceptions and personal contact matter: The individual-level determinants of trust in police in Hungary - Boda, Zsolt (Policing and society, 2017)
In established democracies perceptions about police effectiveness and procedural fairness are the main individual-level determinants of trust in police. However, very little is known about whether this is also the case in different circumstances. By analysing trust in police in Hungary, in an East Central European context, the paper finds that the same micro-level factors have a similar relationship with trust in police there as in established democracies. Both the perceptions of police performance and fairness are significant contributors to trust as well as individual judgements about the country's current affairs. However, people attribute different salience to distinct aspects of procedural fairness: Hungarians are sensitive to police corruption, but less so to discriminative police behaviour. Finally, the overall effect of personal contact with the police on trust is negative, but distinguishing those who reported negative personal experiences from those who were satisfied with how the police treated them shows that only bad contacts have a detrimental effect on trust. Our findings suggest that while positive personal experiences with the police do not improve trust judgements, negative ones damage people's perceptions about the police in virtually every dimension.